(untitled) - Kreuzer, Helen (Washington, D.C., 2001)
Recombinant DNA and Biotechnology: A Guide for Teachers will enable college and precollege teachers to plan and conduct an exciting and contemporary course on the basic principles, essential laboratory activities, and relevant social issues and concerns attendant to today′s molecular biology revolution. In addition to the complete text of the student edition, A Guide for Teachers also contains the answers to all discussion questions and extra background information and material on the scientific principles involved.
Keywords: Recombinant DNA,Tái tổ hợp DNA